Bioinformatics analysis on the expression of GPX family in gastric cancer and its correlation with the prognosis of gastric cancer. Issue 12 (December 2022) - Ye, Siping; Lin, Rui; Guo, Xiao; Xing, Jiaying; Liu, Keyi; Yang, Wenchuang; Guo, Naiyuan
Abstract: Background: Gastric cancer (GC) is one of the most common cancers of the digestive tract, with the fifth-highest incidence and third highest mortality rate in the world. Methods: In this study, the Kaplan-Meier Plotter database was used to analyze the correlation between the expression of the glutathione peroxidase (GPX) family and the clinical prognosis of gastric cancer (GC). The prognostic value of increased GPX family mRNA expression in GC patients in different clinical stages, with different differentiation degrees, in different genders and human epidermal growth factor receptor-2 (HER2) status, and treated with different therapeutic regimens was also studied. Results: The results showed that with the increase of GPX1 and GPX2 mRNA low expression levels, the overall survival (OS) of gastric cancer patients was longer. However, when the high expression levels of GPX3, GPX5 and GPX6 mRNA increased, gastric cancer patients presented good OS, while the increase of GPX4 mRNA expression level had no significant correlation with OS in gastric cancer patients. Conclusion: The results of this study are expected to provide a reliable basis for the clinical treatment of GC and lay a foundation for the development of a novel GC treatment approach. Abstract : Gastric cancer; Glutathione peroxidase (GPX); Prognostic analysis.